Legal Hermeneutics: A Standard and Parameters of Interpretation of the New Criminal Code - Nurmadiah, Nurmadiah; Yamin, Ahmad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The purpose of this study is to investigate how standards and parameter for interpreting the Kitab Undang-Undang Hukum Pidana (KUHP) were developed. Public believes that the KUHP contains a number of contentious sections. This study is a type of qualitative research through library data. It is called library research because data regarding legal interpretation and the formation of standards and parameters are obtained from library materials. The text analysis method with a multidisciplinary, interdisciplinary, and transdisciplinary approach to science will be employed as the data analysis technique. In this study, authoritative and original data serve as the primary source, while supporting data from multiple sources serves as the secondary source. scholarly writings, news articles or official reports, commentary on the recently. This research finds that hermeneutics as legal interpretation serves as a bridge between law and moral ethics. There are 6 standards and parameters in the process of legal interpretation, namely text and legal context analysis, contextual interpretation, methodological interpretation, dialogue between the text and the interpreter, principles of justice and humanity, evaluation, and validity testing. Finally, the results of applying those standards and parameters in examining Pasal 2 ayat (2) KUHP regarding common law emphasize the importance of balancing respect for local wisdom and alignment with national legal principles.